Business Development Strategy and Increasing Online Marketing Technology Capabilities for Superior MSME Products in the Karanganyar Gunung Sub District Candisari Subdidistrict Semarang City - Johanis Souisa; Dwi Widi Pratito; Lauren Instiyawari (Jurnal Insan Pengabdian Indonesia, 2024)
Community Service by Lecturers (PKM) is a tangible form of the implementation of higher education values in contributing to the community. PKM lecturers from the Faculty of Economics, University of Semarang carry out two types of activities, namely socialization and training in using online promotion methods in marketing their products. This socialization and training was held in Karanganyar Gunung Village, Candisari District, Semarang City. The purpose is to provide knowledge with training in the use of online promotion methods in order to anticipate a wide market and to improve the ability of MSME superior product players in planning their business marketing, especially in the use of online media to market their products. Through discussions and delivery of material, as well as in-depth training, this activity is expected to increase knowledge and understanding of online marketing on MSME superior products in the Karanganyar Gunung sub-district area, Candisari District, Semarang City